2011
DOI: 10.1186/2110-5820-1-29
|View full text |Cite
|
Sign up to set email alerts
|

The challenge of admitting the very elderly to intensive care

Abstract: The aging of the population has increased the demand for healthcare resources. The number of patients aged 80 years and older admitted to the intensive care unit (ICU) increased during the past decade, as has the intensity of care for such patients. Yet, many physicians remain reluctant to admit the oldest, arguing a "squandering" of societal resources, that ICU care could be deleterious, or that ICU care may not actually be what the patient or family wants in this instance. Other ICU physicians are strong adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
125
3
9

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 197 publications
(146 citation statements)
references
References 39 publications
9
125
3
9
Order By: Relevance
“…Compared with younger and stronger patients, older and frailer patients admitted to the intensive care unit experience higher rates of mortality and morbidity, affecting quality of life and placing a greater burden on resources. 31,32 The overall increased use of CAM by patients who may think that these therapies are safe and who have little understanding of the potential adverse effects place these patients at increased risk for admission to an intensive care unit. 13 Examples of these effects (see the Table) include acute tubular necrosis (some traditional Chinese and Ayurvedic herbal medicines), severe hemorrhage (Gingko biloba, garlic, ginger), hypertensive crisis and cardiac arrhythmias (ginseng, yohimbe, ephedra), severe electrolyte disturbances (licorice), and cerebrovascular events (spinal manipulation, particularly when performed by nonlicensed practitioners).…”
Section: Implications For Acute and Critical Care Nursesmentioning
confidence: 99%
“…Compared with younger and stronger patients, older and frailer patients admitted to the intensive care unit experience higher rates of mortality and morbidity, affecting quality of life and placing a greater burden on resources. 31,32 The overall increased use of CAM by patients who may think that these therapies are safe and who have little understanding of the potential adverse effects place these patients at increased risk for admission to an intensive care unit. 13 Examples of these effects (see the Table) include acute tubular necrosis (some traditional Chinese and Ayurvedic herbal medicines), severe hemorrhage (Gingko biloba, garlic, ginger), hypertensive crisis and cardiac arrhythmias (ginseng, yohimbe, ephedra), severe electrolyte disturbances (licorice), and cerebrovascular events (spinal manipulation, particularly when performed by nonlicensed practitioners).…”
Section: Implications For Acute and Critical Care Nursesmentioning
confidence: 99%
“…[1][2][3] Older people require more medical services than younger people because of the higher rates of functional impairment and chronic morbidity. [1][2][3][4] Consequently, the number of very elderly patients admitted to the ICU with acute illnesses is increasing. [1][2][3] A study in Australia and New Zealand found an annual increase of 5.6% in the number of ICU patients over 85 y.…”
Section: Introductionmentioning
confidence: 99%
“…Yapılan tahminlere göre 2050 yılına kadar dünyada 80 yaş üstü popülasyonun sayısı ikiye katlanacaktır [3]. Bununla birlikte yoğun bakımda takip edilen hastaların da yaş ortalaması gün geçtikçe artmaktadır.…”
Section: Discussionunclassified
“…Ulusal ve uluslararası çalışmalarda da tanıma uygun olarak genellikle yaşlı ve ileri yaşlı ayrımı için bu yaş grupları kullanılmaktadır [2][3][4]. Ancak yaşlı tanımı için 60 yaş ve üstünün [5] alınması ya da ileri yaş için 75 veya 85 yaş ve üstünün [6][7][8] alınması gibi farklı yaş kriterlerinin kullanımı da söz konusu olmuştur.…”
Section: Introductionunclassified